Optimal channel strategy of luxury brands in the presence of online marketplace and copycats - GAO, Sarah Yini (Institutional Knowledge at Singapore Management University, 2022)
The strategic interaction between authentic luxury brands and their copycats has evolved since the proliferation of online marketplaces. Using a game-theoretic framework, we examine how an authentic luxury brand, observing the strategic behavior of its competing copycats, should make its optimal entry decision to a third-party online marketplace. Our findings reveal that the authentic luxury brand does not sell on the online marketplace when either the quality or the physical resemblance of the copycat to the authentic luxury brand is high. This contributes to the related literature by offering an explanation for the increasing quality of copycats amid the e-commerce boom —improving the quality of the copycat can deter the authentic luxury brand from selling on the online marketplace. Furthermore, by comparing our equilibrium outcome with the benchmark case where the authentic luxury brand does not consider selling on the online marketplace at all, we show that the authentic luxury brand’s potential entry to the online marketplace is sufficient to induce the copycat to improve its quality and lower its price, thereby improving the aggregate consumer surplus. In addition, the online marketplace can always be better off allowing the entry of the copycat if there is no external enforcement against copycats. We show that our key results are valid in various extensions and they offer multiple managerial implications.